Balanced displacement methods and effect evaluation of heterogeneous combination flooding in different reservoirs - Dejun WU; Jian HOU; Lijie LIU; Kang ZHOU; Zhibin AN (工程科学学报)
The synergistic oil production using heterogeneous combination flooding and field adjustment measures achieved good results in increasing oil production and decreasing water cut in the Ng3 block of the Gudao Oilfield. However, because of the complex heterogeneity of the actual formation, differences in the deployment of interlayer well networks, and different injection volumes of chemical agents in different layers, the extraction of planar and vertical remaining oil by heterogeneous combination flooding is affected. Clarifying the contributions of different balanced displacement methods and elucidating the mechanism of extracting the different types of remaining oil are difficult. Therefore, this study establishes five different types of models for remaining oil reservoirs based on the actual formation parameters of target blocks using reservoir numerical simulations. The remaining oil, extracted remaining oil, oil displacement efficiency, sweep coefficient, planar water saturation variation coefficient, and vertical water absorption imbalanced coefficient are used to evaluate the balanced displacement effects of heterogeneous combination flooding. On this basis, the mechanism of the remaining oil extraction was elucidated. The numerical simulation results show that field adjustment measures such as well network adjustment and layered injection allocation for heterogeneous combination flooding can maximize the balanced displacement effect. For different types of remaining oil reservoirs, the priority of implementing balanced displacement methods was clarified. In practical applications, suitable balanced displacement methods should be selected based on the type of reservoir and conditions of the field implementation. In reservoirs with developed high-permeability zones, heterogeneous combination flooding effectively creates advantageous channels for water flow. Meanwhile, well network infilling can increase the swept volume of heterogeneous combination flooding in low-permeability areas and enhance the displacement efficiency of the enriched remaining oil. The balanced displacement effect of heterogeneous combination flooding was better than that of the well network adjustment. In reservoirs with imperfect injection production well networks, improving the well network can increase the sweep range of streamlines, and synergistic heterogeneous combination flooding can dynamically regulate and strengthen the extraction of remaining oil. The balanced displacement effect of well network adjustment is better than that of the heterogeneous combination flooding. In unconnected reservoirs, the enriched remaining oil blocked by faults is difficult to connect with production wells. Thus, well network adjustment can effectively overcome the blocking effect of faults and extract unconnected remaining oil. The balanced displacement effect of well network adjustment is better than that of the heterogeneous combination flooding. In rhythmic reservoirs, injected fluids flow along high-permeability water-flooded intervals. Heterogeneous combination flooding can effectively plug them, thereby increasing the water absorption of weak, low-permeability water-flooded intervals and extracting the high-saturation remaining oil. In interbed reservoirs, layered water injection can significantly improve the degree of vertical water absorption imbalance. Heterogeneous combination flooding further played a role in conformance control and oil displacement at different layers, enhancing the sweep effect and improving oil displacement efficiency, effectively extracting the remaining oil controlled by the interbeds. The effect of heterogeneous combination flooding on improving balanced displacement is better than that of layered water injection, and the layered allocation of heterogeneous combination flooding can achieve vertical balanced displacement to the maximum extent. This study provides a reasonable explanation for extracting different types of remaining oil and achieving balanced displacement for heterogeneous combination flooding and affords reference significance for future promotion and field applications in different reservoirs.